Molecular epidemiology of cutaneous leishmaniasis and inventory of sand flies spatial distribution in Yemen - Ahmed Mohammed Alkhlai, Arwa (Université Ibn Tofail, Faculté des Sciences-Kénitra, 2017)
Since the 70s, several studies have been done in Yemen to know the spread of the leishmaniasis disease, but until now, and in actually, leishmaniasis has not been officially declared as a disease that threatens the lives and health of citizens. It is very important to specify the epidemiological determinants responsible for the transmission of leishmaniasis as wel as the etiological agent, vectors and susceptible hosts. The main objective of this study is to strengthen scientific research in order to contribute to the eradication of leishmaniasis. In addition, three special aimes were considered in this stud. The first is to evaluate the disease in twenty-one Yemen provinces for last eight years; the secibd ficyses ib assessing the incidence of cutaneous leishmaniasis in suspected individuals in nine Yemeni provinces and the third aime is to identify the vector responsible for the transmission of the disease in two regions of Yemen. In the first part of this work, epidemiological and statistical studies of cutaneous leishmaniasis during the last nine years (2005-2013) in twenty-one city of Yemen namely Sana’a, Amran, Aden Taiz, Ibb, AlHodeidah, Hajjah, Thamar, Sa’adah, Al-Mahweet, Rimah, Mareb, Al-Jawf, Albaidah, Aldhale, Abyan, shabwah, Lahaj, Almahra, Soqatra, Hadramawt. The data are provided by Leishmanisis surveillance program in Yemen. Moreover, in the second part, we were interested in identifying the type of leishmaniasis via a microbilogical study, on skin samples were interested in identifying the type of leishmaniasis via a microbiological study, on skin samples were collected from 129 individuals with the disease, public in hospitals and private laboratories in the capital Sana’a (the Al-Thawra hospital, the al-jomhori hospital, the central laboratory, the international laboratories) and Al-Thawra General Hospital in Thamar. During the sampling, we collected the main personal information of the patients like the age, sex, the site of lesion and the place of residence then we treated these data by statistical method (SPSS). Finally, in the third part, over a period of two months, between the months of August and September 2014, we conducted the capture of sand flies that are responsible of this disease by the method of CDC miniature light trap in two regions (Bani Kais and Sawan). In the first part, we recorded a total of 19949 affected by leishmaniasis with an annual average of 2216.5 µ 270.8. The maximum number of patients was reported in 2012 (18%) and the minimum number of patients was recorded in 2007 (5%). The highest infection rates were reported in Sanâa (18%) and Taiz (14%), while the lowest rate was found in Abyan (0.1%). It should be noted that no cases has been recorded in Soqutra an Almahra. In the second part, among 129 cases, we recorded 56% of the positive cases by using microscopic examination, while the technique of polymerase chain reaction indicate at the rate of 43% of cases was positive. Regarding the results of the third part, among 216 sand flies, we distinguished six spp. Of sandflies and ten spp. Sergontomyia, It is mentioned that the P. bergeroti type is represented by the highest rate (68.25%), while the S.squmipleurisi type is represented by the lowest rate (1.11%). In addition, we discovered two spp. Sergontomyia; S.squamipleuris and S.minuta. We concluded that Leishmania tropica is the leading cause of cutaneous leishmaniasis in Yemen. It has been found that the disease is very prevalent in men than in women between the ages of 15 and 65. The high rates of infection were recorded in rural areas. In addition, our study showed the presence of variety spp. of sand fly in Yemen, which leads us to identify new forms of the disease.
Keywords: Cutaneous leishmaniasis; Sand fly; Phlebotomes; Sergontomyia; Leishmania tropica; Yemen.